IMPACTS OF JIGSAW AND TEAMS-GAMES-TOURNAMENTS (TGT) ON SOCIAL STUDIES PRE-SERVICE TEACHERS' EPISTEMOLOGICAL BELIEFS - Ufuk Şimşek; Aşkın Baydar (Informascope, 2019)
Classroom practices of teachers are affected by their personal epistemological beliefs and cooperative learning methods are taking a large place in today's education world. By implementing two different cooperative learning methods in a college of education course, this study examined the effects of jigsaw and teams games tournaments (TGT) on epistemological beliefs of social studies preservice teachers. 30 students participated in the research who attended 4th grade at Artvin Coruh University Social Studies Education department at 2015-2016 academic year. Data were collected with Schommer Epistemological Questionnaire and analyzed by independent groups t-test. The findings elicited that jigsaw is significantly more effective that TGT on social studies preservice teachers' epistemological beliefs in general and for two of the dimensions measured: "the belief that learning depends on effort", and "the belief that learning depends on ability". But for the dimension, "the belief that there is only one unchanging truth", there was no significant differences between two methods. Keywords: cooperative learning, jigsaw, TGT, epistemological beliefs, teacher education.